Життєвий і творчий шлях першого дослідника творчості Миколи Леонтовича Гната Яструбецького - Семенко, Л. (Народна творчість та етнографія, 2006)
Hnat Yastrubetsky was a Ukrainian social and musical life activist in the 1920—1930-th years. He also was a personal friend of Mykola Leontovych. Since his name is still not well known this article draws attention to Hnat Yastrubetsky. The materials presented in this article are based on the materials of the book written by A. Zavalniyk “Mykola Leontovych. Researches, Documents Letters”, and also the description of his life and work given in this paper is based on the materials of various archives, including personal archive of Yastrubetsky family.